Students’ Perception on Using Google Classroom to Improve English Writing Skills - Solihin, Rully Khoeru; Muhria, Lanlan; Wiarsih, Asih; Supriatna, Nana (Qualitative and Quantitative Research Center, 2024)
Google Classroom is a widely used feature by educators to help them submit and organize student assignments. The objective of this study is to ascertain students' perspectives on the utilisation of Google Classroom in English classes. The method used a qualitative research design involving STKIP Yasika Majalengka students who had used Google Classroom in English courses in the first semester with a sample of 120 students. Data was collected via surveys and interviews The acquired data was examined through the process of theme analysis. The findings revealed that college students consider Google Classroom a helpful tool that helps them turn in assignments easily and manage tasks better. Therefore, it can be concluded that Google Classroom is helpful for lecturers and students in improving their writing skills in English courses. The incorporation of technology into education is anticipated to foster the development of a dynamic learning environment. Technology has the potential to enhance the educational process by offering a wide range of tools and resources that assist students and instructors in achieving their learning objectives with greater efficiency. This study contributes valuable insights into students' perspectives regarding using Google Classroom facilities to enhance learning without disrupting the learning process.